PERAN PONDOK PESANTREN RAUDLATUL HUFFADZ BALI DALAM ME-NANAMKAN NILAI MODERASI BERAGAMA - Hifni Laila Nashifah; Alfaina Mafazah Musallamah; M. Fajrul Falah; Silmi Afifah; Widodo Hami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of the Raudlatul Huffadz Islamic Boarding School in Bali in instilling the values ​​of religious moderation in students through a library study approach. The study used a library research method with a qualitative approach. Data were obtained from various sources, such as books, scientific articles, previous research results, and relevant documents, then analyzed using content analysis techniques. The results of the study indicate that the Raudlatul Huffadz Islamic Boarding School in Bali has a significant role in shaping the moderate attitudes of students through religious learning, the example of kiai and ustaz, the habit of living together, strengthening national values, and the application of a culture of tolerance in everyday life. The existence of the Islamic boarding school in the midst of Balinese society, which is predominantly Hindu, also serves as a means for students to learn to live side by side, respect differences, and build harmonious social relationships without reducing their commitment to Islamic teachings. The instillation of religious moderation is supported by a conducive Islamic boarding school environment, a culture of deliberation and mutual cooperation, the competence of educators, and cooperation between the Islamic boarding school, family, community, and government. On the other hand, this process still faces various challenges, such as increasing intolerance, the spread of radicalism through digital media, low digital literacy, and the suboptimal integration of religious moderation values ​​in several educational institutions. Based on the results of this study, it can be concluded that the Raudlatul Huffadz Islamic Boarding School in Bali plays a crucial role in developing the character of religious, tolerant students who are able to live harmoniously in a pluralistic society. Therefore, strengthening religious moderation needs to be carried out continuously through synergy between various parties to create a peaceful, harmonious life and mutual respect for diversity.